Construction of Pancasila Student Mentality through Animation as Student Learning at SMKN 11 Malang - Wardhani, Fitria Maudy; Iriaji, Iriaji; Ratnawati, Ike (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2024)
This research aims to determine the meaning semiotic animation "Pancasila Student" SMKN 11 Malang. In revealing meaning, researcher use Roland Barthes' semiotic analysis technique known as denotation and connotation. Type of this paper is descriptive qualitative. The results of the analysis were obtained from the signs in the form of animation visuals which were explained descriptively and interpretively with the researcher as the main instrument. The results of the semiotic analysis of this visual form, denotative meaning in the form of a boy saluting the Garuda Pancasila with Pancasila attributes and a robe walking past places of worship, bowing to older people, prevent friends which is fighting, not breaking the law, stopping bullying , and finally, it turns out to his past and the connotation that is formed is the profile of Pancasila which is inherent in students' lives which is connoted to have a good impact on society in accordance with the precepts of Pancasila and the law in Indonesia. SMKN 11 conveys the message that today's education that carries Pancasila as one of the most important things taught in school as an ideology so that the values of Pancasila are actualized in every life of society, nation and state.